The role of the Speech Therapist in the Birth Support Courses of the Marche region: proposal for a diagnostic therapeutic assistance pathway. - Biocca, Paola; Tittarelli, Sofia; Verolino, Antonio; Galli, Federica Lucia (Journal of Biomedical Practitioners, 2024)
OBJECTIVE: Proposing a Diagnostic Therapeutic Assistance Pathway (PDTA) that enhances the preventive role of the Speech Therapist within Birth Support Courses (CAN), aiming to raise awareness and enhance parental skills regarding the communicative-linguistic, oro-facial-swallowing, and feeding development of newborns, thereby preventing potential disorders and difficulties in these areas. MATERIALS AND METHODS: A narrative review of the literature concerning Guidelines and PDTAs published in the Marche Region related to the Birth Pathway and Prevention in Early Childhood was conducted. The objective was to synthesize information regarding care models organized to promote and monitor the well-being of future parents during pregnancy and in the months following childbirth, as well as prevention programmes concerning the child’s first 1000 days of life. The project is implemented by hypothetically involving the Territorial Health Companies (AST) of the Marche Region to develop a PDTA addressed to parental couples being comprised according to specific inclusion criteria (age over 18 years, residing in the Marche Region, physiological pregnancy, Italian native speakers or with at least B1 level of Italian language proficiency, consent to participation expressed during recruitment) and exclusion criteria (pregnant women in the period between 0-5 months). Within the various proposed meetings in the CAN, to integrate the activities of the Speech Therapist with those of other professionals, timetables and flowcharts are hypothesized concerning preventive actions for psychomotor and communicative-linguistic development in children aged 0 - 3 years. The healthcare programme also involves defining indicators of structure, process, and outcome. RESULTS: Conceiving a comprehensive and active clinical network, from prevention to empowerment, through a PDTA (Diagnostic Therapeutic Assistance Pathway) tailored on the real needs of parents and developmental age, which involves an interdisciplinary approach to guide the selection of training and informative contents towards understanding oro-sensory experiences and communicative-linguistic aspects, integrating them within family’s environment. DISCUSSION and CONCLUSION: The role of the Speech Therapist in Child Protection Services (CAN) has a preventive objective, supporting the communicative-linguistic and oro-facial-nutritional development of children. Building trust with the various professional figures involved in the PDTA (Diagnostic Therapeutic Assistance Pathway) increases parents’ sense of security and adherence during pregnancy, childbirth, and the postnatal period. The PDTA serves as an appropriate tool for preventing oro-facial and communicative-linguistic issues in developmental age, facilitating the work of the Speech Therapist in interdisciplinary teams, and supporting active participation of families throughout the regional territory of Marche Region. The creation of a comprehensive therapeutic and care pathway aimed at implementing the preventive role of the Speech and Language Pathologist within Childbirth Accompaniment Courses has the objective of enhancing parental awareness and skills as far as communicative-linguistic, oro-facial, swallowing and nutrition development is concerned.